2022
DOI: 10.1186/s13058-022-01532-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-regulated carbonic anhydrase IX (CAIX) protein is an independent prognostic indicator in triple negative breast cancer

Abstract: Background The effect of extracellular microenvironment (hypoxia and pH) has been regarded as a key hallmark in cancer progression. The study aims to investigate the effects of carbonic anhydrase IX (CAIX), a key hypoxia-inducible marker, in triple-negative breast cancer (TNBC) in correlation with clinicopathological parameters and predicting survival outcomes. Methods A total of 323 TNBC cases diagnosed at the Department of Anatomical Pathology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Cancer cells often undergo metabolic reprogramming due to oxygen and nutrient deprivation within solid tumors, resulting in an upregulation of CAIX. Studies have shown that CAIX is a key hypoxia-inducible protein marker, and higher levels of CAIX are associated with poorer survival in patients with TNBC and ovarian, bladder, and lung cancers [ 45 , 46 ]. Additionally, the depletion of CAIX + cells has been shown to reduce the number of cancer stem cells (CSCs) in primary solid tumors and cancer cells in the bloodstream (CTCs) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells often undergo metabolic reprogramming due to oxygen and nutrient deprivation within solid tumors, resulting in an upregulation of CAIX. Studies have shown that CAIX is a key hypoxia-inducible protein marker, and higher levels of CAIX are associated with poorer survival in patients with TNBC and ovarian, bladder, and lung cancers [ 45 , 46 ]. Additionally, the depletion of CAIX + cells has been shown to reduce the number of cancer stem cells (CSCs) in primary solid tumors and cancer cells in the bloodstream (CTCs) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown a correlation between CAIX and poor prognosis or increased metastasis [ 74 , 75 ]. In thyroid cancer, patients with higher CAIX expression have a higher frequency of lymph node metastases [ 76 ].…”
Section: Hypoxic Secretomementioning
confidence: 99%
“…With the exception of renal cell carcinoma, CAIX expression is constitutively upregulated in and strongly correlated with reduced oxygenation status in primary and metastatic sites in several tumor types [15]. CAIX gene expression is associated with poor prognosis and is upregulated in LNMs of patients with breast and cervical cancer, oral cavity squamous cell carcinoma, melanoma, and as demonstrated by Tian et al in this issue of the European Journal of Nuclear Medicine and Molecular Imaging, in occult LNMs and ENEs of primary and recurrent nasopharyngeal carcinomas [15][16][17][18][19][20][21]. Thus, development of CAIX-specific diagnostic and therapeutic agents is emerging as a promising strategy to target hypoxic and metastatic lymph nodes.…”
mentioning
confidence: 92%